Processing of Oyster Meat for Freezing - ]ohn Chellappan, N. (Fishery Technology, 2025)
Experiments were conducted to determine the ideal depuration time for oysters and processing for shucking. A depuration time of 24 h reduced substantially the sand content. Steaming of oysters for shucking yielded better quality meat with good appearance than the hot water dipping method.